2021
DOI: 10.1016/j.jsat.2021.108371
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis awareness, acceptability and potential stigma among medical and non-medical clinic staff in methadone treatment settings in northern New Jersey: The key role of non-medical staff in enhancing HIV prevention

Abstract: Background: HIV prevention is needed among people who use drugs (PWUD) due to mixing sex and drugs, selling/trading sex, and/or injecting drugs. Pre-exposure prophylaxis (PrEP) is an extremely effective biomedical HIV prevention strategy, but uptake remains low among communities most in need of HIV prevention, including PWUD. Previous studies have found that providers are less willing to prescribe PrEP to PWUD, yet PWUD express high levels of PrEP acceptance. More research is needed to understand how people wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Many women who engage in street-based exchange sex and/or injection drug use experience poverty, gender-based power dynamics, social isolation, and violence which serve to undermine safety negotiations [ 12 17 ]. Barriers to health care, including social stigma, fear of arrest, and fear of discrimination by health care providers, further elevate risk of HIV acquisition by increasing avoidance and limiting access to comprehensive HIV prevention services [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many women who engage in street-based exchange sex and/or injection drug use experience poverty, gender-based power dynamics, social isolation, and violence which serve to undermine safety negotiations [ 12 17 ]. Barriers to health care, including social stigma, fear of arrest, and fear of discrimination by health care providers, further elevate risk of HIV acquisition by increasing avoidance and limiting access to comprehensive HIV prevention services [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Details on the sample and study methodology are available in a previous publication. 3 Briefly, research staff compiled a list of methadone clinics in 2 urban, northern New Jersey counties, and contacted these fifteen clinics in January–April 2019 via telephone, email, and in-person visits. Four clinics initially expressed interest, with 2 withdrawing, resulting in a final sample of 30 staff participants across 2 clinics.…”
Section: Methodsmentioning
confidence: 99%
“…1 Identifying potential communitybased points of entry for PrEP care is paramount for addressing disparities among this population. 2,3 Social and structural factors, such as poverty, housing insecurity, stigma, and racism, place PWUD at increased risk for HIV acquisition due to drug-related or sexual behaviors. 4 Outbreaks of HIV associated with injection drug use demonstrate the need for comprehensive HIV preventions efforts for people who inject drugs, 5 in addition to the documented need for HIV prevention services among all PWUD.…”
mentioning
confidence: 99%
“…Past research focusing on drug use stigma has demonstrated inequities in health support and health care (Frank et al, 2021;Jaiswal et al, 2021;Muncan et al, 2020), social and behavioral This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Intersectional Stigmamentioning
confidence: 99%
“…Past research focusing on drug use stigma has demonstrated inequities in health support and health care (Frank et al, 2021; Jaiswal et al, 2021; Muncan et al, 2020), social and behavioral conditions that impact risk for infectious diseases such as HIV and hepatitis C (Walters, Braksmajer, et al, 2020; Walters, Platt, et al, 2021; Walters et al, 2018), and ultimately negative mental and physical health outcomes (Ahern et al, 2007; Latkin et al, 2019). Research has identified the racialized aspect of the War on Drugs, and how drug policies have disproportionately affected communities of color (Alexander, 2020).…”
Section: Intersectionality and Developing An Intersectional Stigma Fr...mentioning
confidence: 99%